2014
DOI: 10.1155/2014/740105
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Effects of Vanadate Exposure: Potential Biomarkers and Oxidative Stress as a Mechanism of Functional Renal Disorders—Preliminary Studies

Abstract: The alterations in the levels/activities of selected biomarkers for detecting kidney toxicity and in the levels of some oxidative stress (OS) markers and elements were studied in male rats to evaluate biochemically the degree of kidney damage, investigate the role of OS in the mechanism of functional renal disorders, reveal potential biomarkers of renal function, and assess the renal mineral changes in the conditions of a 12-week sodium metavanadate (SMV, 0.125 mg V/mL) exposure. The results showed that OS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
(32 reference statements)
1
20
2
Order By: Relevance
“…Simultaneously, our results allowed us to state that exposure to SMV (0.125 mg V per ml) may induce disturbances in the K FD and Zn FD concentrations ( Fig. 64 The mechanism of increased deposition of Zn FD found in the SMV-intoxicated rats is also unknown. On the other hand, we revealed that antagonistic interaction between V and Mg (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Simultaneously, our results allowed us to state that exposure to SMV (0.125 mg V per ml) may induce disturbances in the K FD and Zn FD concentrations ( Fig. 64 The mechanism of increased deposition of Zn FD found in the SMV-intoxicated rats is also unknown. On the other hand, we revealed that antagonistic interaction between V and Mg (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…After removal of the overlying tissue with stainless steel knives, the femurs were washed in 0.9% NaCl, weighed, and stored frozen at À80 1C in a deep freezer HFU 486 Basic § (Thermo Fisher Scientific, Germany) until the time of mineralization and profilometric studies. 54,64 Only the limits of detection (DL, LOD) for elements investigated in the rats' femur and the values determined by us in the selected bone Certified Reference Material (CRM), the analysis of which confirmed the reliability of the proposed approach, not mentioned previously, have been added in the present report and placed in the Results section. 21 1C) obtained from an ultra-pure HLP Spring 5R water system § (Hydrolab, Poland) to separate the proximal and distal femoral epiphysis (PFE and DFE, respectively, regions of the trabecular bone) from FD (a region of the cortical bone).…”
Section: Preparation Of Femurs For Digestion and Profilometric Evaluamentioning
confidence: 64%
See 2 more Smart Citations
“…7). In addition, V can reduce the thiol status [49,59], release some transition metals [60], interact with other elements [49,53,61], and accumulate in certain internal organs including the liver and kidneys [46,56,[62][63][64] evoking hepato-and nephrotoxic effects, respectively ( Fig. 7).…”
Section: <Figure 7>mentioning
confidence: 99%